2010
DOI: 10.1590/s0074-02762010000400010
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability of ultrasound parameters in portal hypertension

Abstract: (r = 0.828-0.869) and splenic index (r = 0.816-0.905) and varied from fair to almost perfect for diameter of the portal (r = 0.622-0.675), splenic (r = 0.573-0.913) and superior mesenteric (r = 0.525-0.607) veins. According to the results, ultrasound is a highly reproducible method for the main morphological parameters of portal hypertension in schistosomiasis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A criticism of PSR is the subjectivity in measurement of spleen bipolar diameter, but studies have shown the latter to be a reliable parameter with excellent reproducibility as measured by both kappa statistic and intra-class correlation coefficient. 42,43 LSM by transient elastography was the second most accurate diagnostic test in this study and has validated diagnostic accuracy for the detection of cirrhosis across mixed aetiologies. 44 Therefore, the advantage is that one test could be used to diagnose cirrhosis and also stratify for OV; however, the precise thresholds for diagnosing OV are yet to be defined.…”
Section: Implications For Clinical Practice and Areas For Future Resementioning
confidence: 59%
“…A criticism of PSR is the subjectivity in measurement of spleen bipolar diameter, but studies have shown the latter to be a reliable parameter with excellent reproducibility as measured by both kappa statistic and intra-class correlation coefficient. 42,43 LSM by transient elastography was the second most accurate diagnostic test in this study and has validated diagnostic accuracy for the detection of cirrhosis across mixed aetiologies. 44 Therefore, the advantage is that one test could be used to diagnose cirrhosis and also stratify for OV; however, the precise thresholds for diagnosing OV are yet to be defined.…”
Section: Implications For Clinical Practice and Areas For Future Resementioning
confidence: 59%
“…The prediction models used in this study can be calculated easily. The inter-observer variability of the spleen diameter and splenic vein diameter is low, which makes the prediction models reproducible (Sebastianes et al, 2010;Gunes and Akturk, 2018). The measurement of lymphocyte ratio by routine blood tests is easy, highly reproducible, and low-cost (Feng et al, 2018;Chisthi, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, much effort has been devoted to finding non-invasive methods of predicting the presence of EVs and HREVs. Currently, non-invasive predictive parameters are predominantly imaging/ultrasonographic and laboratory parameters, including spleen diameter, spleen/liver stiffness, portal/splenic vein diameter, platelet count, platelet count to spleen diameter ratio, Fibrosis-4 score (FIB-4), aspartate aminotransferase to platelet ratio index (APRI), and aspartate aminotransferase to alanine aminotransferase ratio (AAR) ( Giannini et al, 2003 ; Giannini et al, 2006 ; Hong et al, 2009 ; Kim et al, 2010 ; Colecchia et al, 2012 ; Berzigotti et al, 2013 ; Montasser et al, 2014 ; Morishita et al, 2014 ; Rockey et al, 2016 ). A few studies have reported the non-invasive prediction of EVB ( Kothari et al, 2019 ; Wan et al, 2021 ) and large EVs ( Sharma and Aggarwal, 2007 ; Lijing et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the wide utilization of US, some limitations -among others, the one related to reproducibility -, have been attributed to the method (8) . However, most recently it was demonstrated that US presents a high agreement in the evaluation of patients with portal hypertension (11) , reinforcing its utility amongst SM patients.…”
Section: Editorialmentioning
confidence: 93%